Integrated molecular and cellular biophysics - Raicu, Valerica. (Springer, 2017)
This book integrates concepts and methods from physics, biology, biochemistry and physical chemistry into a standalone, unitary text of biophysics that aims to provide a quantitative description of structures and processes occuring in living matter. The book introduces graduate physics students and physicists interested in biophysics research to "classical" as well as emerging areas of biophysics. The advanced undergraduate physics students and the life scientists are also invited to join in, by building on their knowledge of basic physics. Essential notions of biochemistry and biolo.